Structural Analysis of Relationship of Internet Addiction with Depression, Social Adjustment and Self-Esteem - Bidi (پزشکی بالینی ابن سینا, 2012)
Introduction & Objective: Internet has become more widespread, removed borders, and provided the people all over the world with great opportunities. Notwithstanding this, the consequences especially in social and cultural context must not be neglected. One of the harmful aspects of internet is internet addiction disorder. The present study aimed to survey and analyzes internet addiction relationship with depression, social adjustment, and self esteem. Materials & Methods: Our research method is descriptive-correlational. By random sampling and offline method, we have selected a sample consisting of 120 persons from Dubai coffee net users with different native languages, 74males and 46 females, aged at least 18 years old and proficient in the English language. Research tools were young internet addiction test (IAT) with reliability α=0.88, Beck depression inventory with reliability α=0.84, Sinha social adjustment with reliability α=0.92 and Eysenck self esteem inventory with reliability α= 0.87. The data was analyzed with path analysis method. Results: The results from analysis showed that the data has goodness of fit with the presented model (χ2=3.17 df=3 P=0.36 GFI= 0.99 AGFI= 0.96 CFI= 1.00 NFI= 0.97 RMSEA=0.02). Scales means in internet addiction was 47.69±17.75 depression 21.29 ± 11.12 social adjustment 19.75±7.91 and self esteem was 15.16±4.16. Path coefficient showed that depression (β= 0.57 t=7.61), social adjustment (β= -0.55 t=13.1) and self esteem (β= -0.32 t=14.8) have significantly predicted internet addiction Conclusion: Internet is an important means in the today’s world, but we have to be fully aware of its dangers .In order to avoid the risks of internet use, vast national and international culture-building activities should be done. The results of our research proved the above-mentioned hypothesis.